The Role of Acetylcholine Esterase in Resistance Mechanism of Plutella xylostella to Emamektin Benzoate - Udi Tarwotjo; Rully Rahadian (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2018)
One of the resistance mechanism of P. xylostellato emamektin benzoate is target insensitivity which is acetylcholine esterase that responsible for resistance occurrence. The objective of this study was to determine the role of acetylcholinesterase in the resistance mechanism of P. xylostella population to emamektin benzoate. For enzyme activity analysis, larvae homogenate of the third instar of P. xylostella was prepared. The number of insects required for each scour is 1 for each field population. The protein content in P. xylostella homogenate was measured by the Folin-Ciocalteu test. Non-specific esterase activity with an absorption rate was read using ELISA reader tool with Î» = 450 nm.Â The inhibition level of acetylcholinesterase activity by emamectin benzoate in the tested population was 36.84%. The highest inhibition occurs in Puasan (Ngablak) population.Â The result shows that a Î±-naphthyl acetate substrate was used so that it was recorded as non-specific esterase activity and did not exhibit esterase activity which specifically describes emamectin benzoate. Non-specific esterase enzyme activity of either Î± or Î²-naphthyl acetate substances to benzoic emamectin in the tested population most of the population was still susceptible. On Î±-naphthyl acetate substrate, the highest absorbance value found in susceptible population to benzoate emamectin (0.773), while the lowest found in Babrik (Ngablak) populationÂ (0.083).